1995
DOI: 10.1021/ma00110a027
|View full text |Cite
|
Sign up to set email alerts
|

Study of Poling and Relaxation in Kink and Linear Main-Chain-Functionalized Polymers for Second-Order Nonlinear Optical Applications

Abstract: The rotational dynamics of nonlinear optical chromophores functionalized to polymer main chains were studied using second harmonic generation. Corona poling was used to orient the chromophores into the bulk noncentrosymmetric structure required to observe second-order nonlinearity. In order to detect different microscopic relaxation mechanisms of the polymers, chromophores were incorporated into the polymer main chain but positioned in two different ways. It was found that for a kink polymer, in which the chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 0 publications
1
14
1
Order By: Relevance
“…Köhler et al 12,13) studied the relaxation of electric field induced polar orientation in main-chain polymers. Stenger-Smith et al 65,66) , Lindsay et al 67) , Wrigth et al 68,69) and Liu et al 70) also synthesized main-chain polymers, but the reported second-order susceptibilites were low (0.17 pm/V). A polyurethane main-chain polymer with dialkylamino sulfonyl azobenzene incorporated in the main chain was studied by Xu et al 71) They measured a d 33 (-2 x; x, x) value of 40 pm/V (T g not given, poled at 115 8C, excitation at 1 064 nm).…”
Section: Main-chain Polymersmentioning
confidence: 99%
“…Köhler et al 12,13) studied the relaxation of electric field induced polar orientation in main-chain polymers. Stenger-Smith et al 65,66) , Lindsay et al 67) , Wrigth et al 68,69) and Liu et al 70) also synthesized main-chain polymers, but the reported second-order susceptibilites were low (0.17 pm/V). A polyurethane main-chain polymer with dialkylamino sulfonyl azobenzene incorporated in the main chain was studied by Xu et al 71) They measured a d 33 (-2 x; x, x) value of 40 pm/V (T g not given, poled at 115 8C, excitation at 1 064 nm).…”
Section: Main-chain Polymersmentioning
confidence: 99%
“…Eventhough lamellar crystals of ferroelectric V Fl-F3 E are polar they are randomly oriented giving rise to a macroscopic absence of polarization. The application of a high electric field by the poling process produces an orientation of the dipoles [15] which is stable enough to give rise to a non-linear optical behaviour. The design of non-linear optical polymeric materials typically involve the addition of non linear optical cromophores to a polymer matrix or the incorporation of the cromophore as part of the polymer chain [3, 161.…”
Section: Resultsmentioning
confidence: 99%
“…Ferroelectric V F2-F3 E copolymers are suitable materials to obtain non-linear optical properties without especial modifications. It is interesting to mention that these copolymers additionally to SHG exhibit electrooptic effects depending on molar composition [15].…”
Section: Resultsmentioning
confidence: 99%
“…One is to use a crosslinking method4, 5 and the other is to utilize high T g polymers such as polyimides 6–8. Polymers with NLO‐chromophores in the main chain9–11 or in the side chain12–14 were prepared and investigated. Main‐chain NLO polymers have good thermal stability of dipole alignments, but they often do not dissolve in organic solvents, and their intractability makes them impossible to fabricate stable non‐centrosymmetric films.…”
Section: Introductionmentioning
confidence: 99%